(untitled) (JS (JURNAL SEKOLAH), 2020)
Abstract: Development of Media in the Form of Infographics in Learning History at the High School Level. This study uses research and development methods that refer to the development stage of Borg & Gall and Dick & Carey. The subjects of the study were the students of class X TKR in Tamansiswa Lubuk Pakam Vocational School. Data collection was carried out using a questionnaire. The conclusion of this study is that the media in the form of infographics are feasible to be applied in learning, the assessment of the material experts and the media experts are 75% material experts (including Valid criteria) and 85% media experts (including Very valid criteria). Meanwhile, assessments given by students in the one to one test stage, small class test, and large class test were respectively 79% (including Valid criteria); 83.3% (including Very Valid criteria) and 85% (including Very Valid criteria). Based on the results of the study it can be concluded that the media in the form of infographics meet the eligibility criteria in the history of learning media. Keywords: infographic media, history learning, high school Abstrak: Pengembangan Media Berbentuk Infografis Dalam Pembelajaran Sejarah di Tingkat SMA. Penelitian ini menggunakan metode penelitian dan pengembangan yang mengacu pada tahap pengembangan Borg & Gall dan Dick & Carey. Subjek penelitian adalah siswa kelas X TKR SMK Swasta Tamansiswa Lubuk Pakam. Pengumpulan data dilakukan menggunakan angket. Kesimpulan dari penelitian ini adalah Media berbentuk Infografis layak diterapkan dalam pembelajaran, penilaian dari ahli materi dan ahli media masing-masing adalah ahli materi 75% (termasuk kriteria Valid) dan ahli media 85% (termasuk kriteria Sangat valid). Sementara itu, penilaian yang diberikan siswa pada tahap uji one to one, uji kelas kecil, dan uji Kelas besar masing-masing secara berturut-turut 79% (termasuk kriteria Valid); 83,3% (termasuk kriteria Sangat Valid) dan 85% (termasuk kriteria Sangat Valid). Berdasarkan hasil penelitian dapat disimpulkan bahwa media berbentuk Infografis memenuhi kriteria kelayakan dalam media pembelajaran sejarah. Kata kunci : media infografis, pembelajaran sejarah, SMA